1979
DOI: 10.1111/j.1939-0025.1979.tb02652.x
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory approach to self-blame and self-derogation by rape victims.

Abstract: Quantitative and interview data on rape victims' self-evaluation and attributions of personal responsibility were studied to explore the relevance of theories of "defensive attribution" and maintenance of belief in a "just world." Clinical implications of the findings for adjustment of victims, counseling, victim compensation, and the legal system are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
2

Year Published

1983
1983
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 11 publications
0
25
0
2
Order By: Relevance
“…Possibly, the more extreme the posttraumatic symptomatology, the greater the need to defend against the pain it entails by taking responsibility for causing the traumatic event. However, even if that were the case, the fact that the particular type of defense typical to rape survivors echoes derogatory social views about rape victims (e.g., Lebowitz & Roth, 1994;Libow & Doty, 1979) underscores the societal adversities that rape survivors must routinely deal with, unlike other trauma victims, and the added emotional burden that this entails. The causality may also be circular, such that socially inculcated self-blame contributes to PTSD exacerbation which further worsens the tendency to hold oneself responsible for the rape.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Possibly, the more extreme the posttraumatic symptomatology, the greater the need to defend against the pain it entails by taking responsibility for causing the traumatic event. However, even if that were the case, the fact that the particular type of defense typical to rape survivors echoes derogatory social views about rape victims (e.g., Lebowitz & Roth, 1994;Libow & Doty, 1979) underscores the societal adversities that rape survivors must routinely deal with, unlike other trauma victims, and the added emotional burden that this entails. The causality may also be circular, such that socially inculcated self-blame contributes to PTSD exacerbation which further worsens the tendency to hold oneself responsible for the rape.…”
Section: Discussionmentioning
confidence: 91%
“…In accordance, the harsh social reactions give way to severe culturally inculcated self-blame (Frazier, 1990;Koss & Harvey, 1992;Roth & Lebowitz, 1988;Ulman,1999), across varied cultural and ethnic backgrounds (Neville, Heppner, Oh, Spanierman, & Clark, 2004). The internalized collective charges of victim precipitation regularly turn into self-condemnation, even though in reality they are entirely counterfactual (Arata & Burkhart, 1996;Kilpatrick and Veronen, 1983;Lebowitz & Roth, 1994;Libow & Doty, 1979;Miller, Handley, Markman, & Miller, 2010;Ulamn, 1996). Moreover, rape victims have been shown to fault themselves for not preventing their own assault in correspondence with the degree to which they perceived non-consensual sex to be viewed as legitimate in their social milieu (Miller et al, 2007).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…However, the relationship between the belief in a just world and adjustment to sexual violence has not been investigated systematically. The only possible exception is a study by Libow and Doty (1979), who found a strong negative relationship between the belief in a just world and victims' tendencies to derogate themselves as a reaction to experiencing sexual violence. Yet, conclusions from this study are at best preliminary, because the sample consisted of only seven participants.…”
Section: Belief In a Just World And Dealing With Sexual Violencementioning
confidence: 90%
“…Numerous research efforts showed that the belief in a just world serves as a buffer that protects SWB (Dalbert, 1997;Dalbert, 1998;Dalbert, 2002;Dalbert & Dzuka, 2004;Dzuka & Dalbert, 2002;Libow & Doty, 1979;Lipkus & et al, 1996). It becomes even more important when it comes to preservation of SWB during adolescence.…”
Section: Introductionmentioning
confidence: 99%